The Role of Digital Technology in Sustainable Public Asset Management in Malang City - Fairuzabadi, Ahmad; Afrianto , Eko; Pratama, Lionardi Ursaputra; Muhammad Yusuf Bahtiar (PANGRIPTA, 2025)
Public asset management is a critical component of urban governance, yet many local governments face persistent challenges related to efficiency, transparency, and sustainability. This study investigates the role of digital technology in transforming public asset management in Malang City, Indonesia, a mid-sized urban center seeking to modernize its governance systems. A qualitative descriptive design was applied using a qualitative survey distributed to 42 stakeholders, including municipal officials, IT staff, community representatives, and digital practitioners. The open-ended responses were analyzed thematically, supplemented by document analysis of Malang’s Smart City reports and official statistics. The results show that the adoption of Geographic Information Systems (GIS), Internet of Things (IoT) monitoring, and blockchain-secured records has significantly improved asset registry accuracy, maintenance scheduling, and decision-making efficiency. Transparency and citizen participation have increased through online dashboards and reporting applications, fostering greater public trust. Furthermore, digitalization has supported sustainability objectives by reducing energy consumption, enabling climate resilience planning, and aligning asset management practices with Sustainable Development Goals. Nevertheless, the study also reveals persistent challenges, including limited funding for system upgrades, uneven digital literacy among staff and citizens, and regulatory constraints that hinder data integration across agencies. These findings contribute to the growing literature on digital governance by providing empirical evidence from a non-metropolitan Indonesian city and demonstrating how digital transformation can simultaneously enhance efficiency, transparency, and sustainability in public asset management.